Catalytc cracking of palm oil to gasoline using zeolite catalysts - Siregar, Tirena Bahnur (2005)
The refined, bleached and deodorized palm oil (RBDPO) was converted to gasoline by passing its vapor through catalyst in a fixed bed reactor at atmospheric pressure. The resulting gas and liquid products were analyzed with a gas chromatograph. The catalysts were characterized with X-ray diffraction (XRD), Pyridine absorption-infrared spectrophotometry (Py-IR) and nitrogen adsorption (NA) methods. The selection of a promising zeolite for palm oil cracking using H-ZSM-5 and H-Beta catalyst was performed with reaction temperature ranging from 450°C to 525°C and a weight hourly space velocity (WHSV) of 2.5h-1. The H-ZSM-5 produced the best results with 96.12 wt% palm oil conversion and 29.92 wt% of gasoline selectivity at 525°C. The gasoline contained mostly naphthenes, followed by isoparaffins, aromatics, and olefines. Pretreatment of H-ZSM-5 at hydrogen (H2) flow rate of 1 L/h for 1 hour gave higher gasoline selectivity and conversion of 34.96 wt% and 95.7 wt% at 500°C. Increasing the H2 flow rate for pretreatment catalyst decreased the conversion and gasoline selectivity. The gasoline composition was enriched with naphthenes, aromatics and isoparaffins. Loading copper (Cu) on H-ZSM-5 from 2 wt% to 8 wt% decreased the conversion and gasoline selectivity. Consequently, highest conversion of 86.30 wt% and gasoline selectivity and 19.53 wt% was obtained with 2 wt% of Cu-ZSM-5 catalyst. Copper loading effected in the decreasing of crystallinity, surface area and Brönsted acidity of HZSM-5. Gas as side products consisted mainly of C3 and C4 compounds. The coke was obtained about 1 wt%.